The impact of hot roll temperature on the microstructure and corrosion resistance of super duplex stainless steel, which is used to coat mild steel in seawater environments - Naffat L.; Anwar M.S.; Paristiawan P.A.; Syahid A.N.; Hakim R.N.; Lestari Y.; Perkasa M.; Prijono K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A new material that can be used to replace single steel in high-strength tanks is mild steel cladding Super Duplex Stainless Steel (SDSS). The method of producing multilayer Super Duplex Stainless Steel (SDSS) is the cladding of mild steel Many processes are carried out such as welding Plasma Direct Energy Deposition (DED), laser, and electro-slag strip. In the manufacturing industry, hot rolling is a simple process. Because the procedure is quick and uses inexpensive, traditional equipment, it is referred to as a simple method. The use of seawater was chosen because salty conditions favour corrosion. In this work, the effects of temperatures of 900°C, 1000°C, and 1050°C on the microstructure and corrosion resistance of hot rolled materials are investigated. The investigation of corrosion resistance by examining the microstructure and material properties using metallography, X-ray diffraction, Electrochemical Impedance Spectroscopy (EIS), and Scanning Electron Microscope (SEM) is the main goal of this work. The results of the study demonstrated that when the hot rolling temperature was increased, carburization and decarburization occurred and the corrosion resistance decreased.